Enhancing healthcare leadership in Gujarat, India: an effectiveness study - Panchamia, Jallavi; Chavda, Neha; Sharma, Bharati; Kadri, A. M.; Iyer, Veena (Frontiers in Public Health, 2025)
BackgroundThe state government of Gujarat, India, recognized the need for a systematic leadership enhancement program in 2022 for mid- and senior-level government technical health officials to address complex health system challenges. The Health Leadership Enhancement Program (HLEP) was designed and implemented using the LEADS framework for approximately 150 Public Health and Healthcare leaders in Gujarat, in three cycles, to meet this demand.MethodsThis paper aims to assess the effectiveness of the Healthcare Leadership Enhancement Program using Kirkpatrick’s four-level framework. We evaluated the program’s effectiveness through the four levels: Reaction, Learning, Behavior, and Results.ResultsOver 97% of participants reported having significantly positive reactions to the program’s content and its relevance to their leadership roles. Most participants reported the highest learning under self-awareness and people management. The participants’ subordinates perceived a behavioral shift in the leadership approaches of their leaders. System-level changes were at the level of local work sites rather than at the broad policy level. The participants rated case studies, mentoring, and practice-based assignments as favorable methods under program pedagogy.ConclusionLeadership enhancement programs designed to match work contexts and experiential pedagogy have the potential to enhance individual self-awareness and team management. Real-world case studies, mentoring, and practice-based assignments accompanied by classroom learning seem to be the better pedagogy.